The invention of race : black culture and the politics of representation - Lott, Tommy Lee, 1946- (Blackwell, 1999)
Racist discourse and the Negro-ape metaphor. Slavery, modernity, and the reclamation of anterior cultures. Frederick Douglass on the myth of the Black Rapist. Du Bois on the invention of race. Black consciousness in the art of Sargent Johnson...